Law, reason and religion : a study of selected aspects of the relationship between law and Christian theology - Rowe, Michael C (Rhodes University, Faculty of Divinity, Department of Divinity, 1964)
One cannot say what meaning the theologian ordinarily gives to 'law' as a secular term, no doubt he would claim to give it a 'plain, unambiguous meaning ' such as a rule of conduct imposed by society and enforced by sanctions'. Perhaps this will do for ordinary purposes, but there are some who tend to import an emotive meaning into the term. They understand the term 'law' in a perjorative sense as being mechanical and and coercive, requiring only literal obedience and therefore opposed to faith which is personal, free, and a response not of obedience but of love. It does not seem to occur to them. that the average person freely accepts law as binding, or that sometimes there may be no sanction for not observing a rule of law, or that law is not static but dynamic, constantly changing. Chap. 1, p. 4.
Keywords: Law (Theology); Law and gospel; Faith and reason